(untitled) (Rivista Italiana di Filosofia Analitica Junior, 2012)
One of the ways of analysing the relationship between music and emotions in through musical expressiveness. As the theory I discuss in this paper puts it, expressiveness in a particular kind of music’s secondary quality or, to use the term which gives the theory its name, a disposition of music to arouse a certain emotional response in listeners. The most accurate version of the dispositional theory is provided by Derek Matravers in his book Art and Emotion and in other papers: what I will try to do, then, is to illustrate Matravers theory and claim that it is a good solution to many problems concerning music and its capacity to affect our inner states.